A formulation of neem cake seeded with Bacillus sp. provides control over tomato Fusarium crown and root rot. Issue 3 (4th March 2017) - Lin, Fei; Liu, Niu; Lai, Duo; Kang, Xiang Hui; Pang, Neng Wen; Jiang, Hong Kai; Xu, Han Hong
ABSTRACT: Fusarium crown and root rot (FCRR) caused by the fungus Fusarium oxysporum f. sp. radicis-lycopersici is a damaging soil-borne disease of tomato. A plant growth rhizobacterium, Bacillus sp. strain HN09 isolated from neem tree rhizosphere soil, was shown to inhibit the growth, germination and development of normal morphology of the FCRR pathogen. A substantial level of disease control was achieved in greenhouse trials by soil supplementation with a preparation of neem cake seeded with HN09. Dry sterilisation of neem cake before fermentation gained comparable disease control effect as those in the unsterilised treatment, whereas moist sterilisation treatment decreased the effect significantly. This bioformulation also led to significantly raised activities in tomato genes encoding pathogenesis-related proteins, hence providing an effective alternative for the control of FCRR, reducing the need for chemical fungicide and fertilisers that impact the environment.